2019
DOI: 10.1111/cts.12647
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Nephropathy in Type 2 Diabetes: An Analysis of the ACCORD Trial Applying Machine Learning Techniques

Abstract: Applying data mining and machine learning (ML) techniques to clinical data might identify predictive biomarkers for diabetic nephropathy (DN), a common complication of type 2 diabetes mellitus (T2DM). A retrospective analysis of the Action to Control Cardiovascular Risk in Diabetes (ACCORD) trial was intended to identify such factors using ML. The longitudinal data were stratified by time after patient enrollment to differentiate early and late predictors. Our results showed that Random Forest and Simple Logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 33 publications
0
41
0
Order By: Relevance
“…It was not our goal for this model to be used for individual level patient care. Our model was trained on data from over 1.5 million patients from Ontario, which is among one of the most diverse populations in the world and, to our knowledge, one of the largest prediction modelling studies that takes into account multiple types of diabetes complications [22][23][24][25][26][27][28][29][30][31][32][33][34][51][52][53] . Our model was also wellcalibrated and showed good discrimination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not our goal for this model to be used for individual level patient care. Our model was trained on data from over 1.5 million patients from Ontario, which is among one of the most diverse populations in the world and, to our knowledge, one of the largest prediction modelling studies that takes into account multiple types of diabetes complications [22][23][24][25][26][27][28][29][30][31][32][33][34][51][52][53] . Our model was also wellcalibrated and showed good discrimination.…”
Section: Discussionmentioning
confidence: 99%
“…Many prognostic models have been developed for diabetes complications in the clinical setting [22][23][24] , including more recent applications of machine learning approaches [25][26][27][28][29][30][31][32][33][34] . These models generally have made use of rich suites of features (e.g., body mass index, smoking status, biomarkers ranging from commonly ordered lipids to extensive genetic panels) extracted from electronic medical records (EMRs) 25,27,[31][32][33] or clinical trials 28,30 . However, while these models are important for clinical level risk prediction, they are not easily deployed by governments or private health insurance providers at the population level-which is precisely what is needed for addressing the aforementioned systemic barriers to diabetes complications care 35,36 .…”
Section: Introductionmentioning
confidence: 99%
“…Health outcome prediction models had been developed using methods of machine learning over recent years [ 14 , 15 ]. Some examples included prediction of postoperative in-hospital mortality [ 16 ], complications in patients with diabetes mellitus [ 17 ], and occurrence of cardiovascular diseases in patients on dialysis [ 18 ]. For smoking cessation, a decision tree model developed with machine learning to predict smoking cessation treatment outcome was proposed by Coughlin et al in 2018 [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had shown that dyslipidemia was a well-established risk factor for the renal impairment in diabetes; it is not only associated with the occurrence [ 2 , 10 , 19 ] but also the deterioration [ 4 , 11 ] of DKD. A cross-sectional study published in 2014 involving 13 countries reported the plasma lipid's contribution to the occurrence of DKD; hypertriglyceridemia significantly increased the risk of DKD, and high HDL-C was a protective factor [ 10 ].…”
Section: Discussionmentioning
confidence: 99%